Philippine regional cuisine - Melchor, Jose Antonio Miguel R.; Vizconde, Angelie Marie L. (Manila : Edric Publishing House, 2024)
The Philippines is a country with beautiful nature and delicious foods. It is a land of diversity, in which history and present mix, offering a great variety of cultures, languages and foods.
Chapter 1. Philippine Cuisine -- Chapter 2. History of the Philippines & Its Food: A Timeline -- Chapter 3. Native Ingredients -- Chapter 4. Luzon Cuisine -- Chapter 5. Mindanao Cuisine -- Chapter 6. Mindanao Cuisine -- Chapter 7. Cooking Methods -- Chapter 8. Philippine Condiments.
Include references.
Keywords: COOKING, PHILIPPINE